Is Simulating Casino Environments in Video Games Worse than Gambling with Loot Boxes? The Case of the Removed Pokémon Game Corner - Laato S (Germany, 2022)
Abstract. This study focuses on the effectiveness of video game age ratings to take into account gambling. As a case example, we look at games in the Pokémon franchise where a casino-resembling “game corner” was either completely removed or its features were cut in order to abide by the PEGI (Pan-European Game Information) age rating rules. We argue that the removal of the game corner or its features is tied to an outdated idea of what gambling is, and is focused on removing associations to traditional forms of gambling rather than removing actual modern forms of gambling, such as loot boxes, from games. We address the difficulty of objectively identifying game mechanics that are linked to gambling and discuss the alternative measures game age raters can take to detect and identify gambling in video games. Finally, we discuss the ethical responsibility of game designers in creating gameplay for children that encourages gambling.
Proceedings of the Conference on Technology Ethics, Turku, Finland, October, 21, 2020